Measurement of the absolute n p scattering differential cross section at 194 MeV - M. Sarsour (2018)
We describe a double-scattering experiment with a novel tagged neutron beam to measure differential cross sections for n p backscattering to better than ±2% absolute precision. The measurement focuses on angles and energies where the cross section magnitude and angle dependence constrain the charged pionnucleon coupling constant, but existing data show serious discrepancies among themselves and with energy-dependent partial-wave analyses. The present results are in good accord with the partial-wave analyses, but deviate systematically from other recent measurements. © 2005 The American Physical Society.